Information-Seeking Behavior of Greek Nursing Students: A Questionnaire Study. Issue 2 (February 2017) - Intas, George; Kostagiolas, Petros; Zavras, Dimitris; Chalari, Eleftheria; Stergiannis, Pantelis; Toylia, Georgia; Niakas, Dimitris
Abstract : The aim of this study was to investigate factors influencing the use of electronic journals by nursing students through identification of information needs, information resources used, and barriers to seeking information. A cross-sectional study was conducted using a specially designed structured questionnaire. Of 600 nursing students, 505 agreed to participate, indicating a response rate of 84.2%. Participants sought out nurses and doctors, printed materials, scholarly databases/e-journals, and seminars as information resources. Participants reported that they searched for information for themselves, parents, and inpatients. Most searched for information for diet or special nutrition needs and for specific diseases. The obstacles faced included lack of time and cost. Training in information literacy is important to enhance the skills of nursing students.